2019
DOI: 10.1155/2019/3851576
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition in Skin Cancers: A Review

Abstract: Epithelial-mesenchymal transition (EMT) is involved in physiologic processes such as embryogenesis and wound healing. A similar mechanism occurs in some tumors where cells leave the epithelial layer and gain mesenchymal particularities in order to easily migrate to other tissues. This process can explain the invasiveness and aggressiveness of these tumors which metastasize, by losing the epithelial phenotype (loss of E-cadherin, desmoplakin, and laminin-1) and acquiring mesenchymal markers (N-cadherin). Comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 109 publications
(130 reference statements)
0
47
0
Order By: Relevance
“…EMT is involved in the metastatic progression of various malignancies. [20][21][22] We measured the expression of EMTassociated factors to determine the EMT process after knocking-down the expression of CMTM2. As compared to Huh-7-NC cells, the epithelial markers E-cadherin and…”
Section: Down-regulated Cmtm2 Promotes Hcc Metastasis Through Inducinmentioning
confidence: 99%
“…EMT is involved in the metastatic progression of various malignancies. [20][21][22] We measured the expression of EMTassociated factors to determine the EMT process after knocking-down the expression of CMTM2. As compared to Huh-7-NC cells, the epithelial markers E-cadherin and…”
Section: Down-regulated Cmtm2 Promotes Hcc Metastasis Through Inducinmentioning
confidence: 99%
“…Markers of EMT are the increase of Slug [ 15 ] and a decline of E-cadherin [ 16 ] expression. Notably, the presence of HGF promoted Slug expression ( Figure 4 B) and affected the staining of E-cadherin (E-CAD) ( Figure 4 C), but the co-treatment with DPI counteracted these effects.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research reported that the abundant expression of CCL18 examined in OSCC could promote the growth and metastasis of cancer cells, and was therefore associated with the TNM stage of oral cancer patients 8 . The metastasis of cancer cells is typically accompanied by a decrease in expression levels of epithelial cell markers (e.g., E-cadherin) and an increase in expression of mesenchymal markers (e.g., N-cadherin, ZEB2, ZEB1, Vimentin, Slug and Twist, among others) 22 , 23 , angiogenesis-related factors (e.g., vascular endothelial growth factor (VEGF)) 24 , and matrix metalloproteinases (e.g., MMP-9 and MMP-2) 25 . The exogenous CCL18 stimulation in OSCC cells was shown to cause a decrease in E-cadherin expression and an increase in N-cadherin and slug expression, suggesting that CCL18 could promote EMT in OSCC cells 26 .…”
Section: Discussionmentioning
confidence: 99%